Polar bear cage at the Woodland Park Zoological Gardens, n.d. - University of Washington Libraries. Special Collections Division. (1908)
Caption on image: Polar bear cage, Woodland Park. Seattle Filed in: Seattle--Parks--Woodland Park To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number